Volunteers and management factors in nonprofit organisations: a brief literature review - Ferreira, Marisa R. (2013)
The objective of this paper is to review and discuss the literature about the management factors that can influence volunteer work. First we present the different management factors. This discussion is followed by the identification of the key management factors in volunteering: recruitment, training and rewarding. Finally, we present two main gaps in the literature that justify the scope for further research: (i) how management factors (recruitment, training and rewarding) influence volunteers’ satisfaction and retention; and (ii) predominance of the investigations in the North American context, followed by English and Australian context.